Metrics for software conceptual models - Genero, Marcela, 1966-; Piattini, Mario, 1966-; Calero, Coral, 1968- (Imperial College Press, 2005)
The idea that "measuring quality is the key to developing high-qualitysoftware systems" is gaining relevance. Moreover, it is widelyrecognised that the key to obtaining better software systems is tomeasure the quality characteristics of early artefacts, produced atthe conceptual modelling phase
Keywords: Computer software -- Mathematical models.; Logiciels -- Modèles mathématiques.; REFERENCE -- General.; Computer software -- Mathematical models